PORTRAIT OF HEGEMONY IN THE FILM SOUND APRIL: A CRITICAL DISCOURSE ANALYSIS - RISALDI, ANTOK (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
The April Voice Film is a film that contains education for the public in politics, how to carry out elections healthily and how to defend voting rights for common welfare. The purpose of this study is to find out the meaning of speech and gestures that contain elements of hegemony in films. This research is a type of qualitative research oriented to the analysis of critical discourse to analyze the existence of hegemonic elements in the April sound film. Using data sources from the KPU RI youtube and snippets of several scans as analysis data. The analysis of hegemony in the April sound film uses the fairclough critical discourse analysis technique. to interpret, identify and understand and can be a strong framework in analyzing the power maintained by the anti-political culture in the film Suara April. The research findings are in the form of several scane pieces that contain hegemonic elements and the impact of the hegemony. By using critical discourse analysis, it can be identified through writing, actions, gestures and facial expressions displayed contain hegemony in a group that has a significant impact on the surrounding community. Hegemony is not in the form of coercion or oppression to maintain power but rather leads to thoughts, perceptions that are given consistently so that the community without coercion accepts these thoughts so that together the community rejects election counseling carried out by democracy volunteers.